PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG PADA JEGEG BALI JAYANTI DI KABUPATEN BADUNG - I Gede Suryawan; I Made Adi Suwandana (Jurnal AKSES, 2020)
Repurchase readability happens if the customers satisfied in the previous purchase, and it does not rule out the possibility for them to repurchase the order. Repurchase readability is influenced by product quality and customer satisfaction. In relation to the impact of customer satisfaction’s influenced by product quality toward customer repurchase readability on Jegeg Bali Jayanti in Badung Regency indeed needed further analysis since problem found regarding to product quality and customers satisfaction in order to increase the readability of repurchase. The aim of this study is to find out the relation toward product quality influences the readability of repurchase and customer satisfaction. The writer used 100 samples of customers in Jegeg Bali Jayanti collected through non probability sampling. The data were analyzed by the classic assumption method and path analysis. The finding showed the customer satisfaction’s variable mediate the influence of product quality towards the readability of purchase.